CONFLICTS AMONG STUDENTS: THE FORMATION OF TOLERANT RELATIONS - ANIKIN, IGOR; LAPTEVA, SVETLANA; KOZLOV, ANATOLIY (The journal of contemporary issues in business and government, 2021)
Conflict is an integral part of human life. Any human community makes conflict possible. Every company no meter job or study needs comfortable communication, and often it is necessary for creating a harmonious and productive microclimate in a team. The right approach to resolving conflicts allows us to relieve tension, and to find a compromise, to develop a consensual movement vector to achieve the goals. The student community is always the most creative, movement, and socially active. This social range is usually a universal engine of social, technical, cultural, and moral changes in every country all the world. And it is important to form progressive, smart, and tolerant young generation. This is able for High School to do. Forming tolerant relations becomes an important part of professionals creating. The high school has a unique opportunity to form a culture-and-moral model of behavioral co-existence, it allows to make the individual initiative significant, to consolidate interest and to reveal the hidden resources in the professional personality formation process.